Parenting Practices of Some Gay Men in Mexico City. Between Taboos and New Bets for their Practice - Giraldo Aguirre, Sebastián (Sociedad y Economía, 2015)
Although the paternity of gay men has achieved prominence in recent years, the ways they manage their paternity are unknown yet. This article outlines the parenting practices of four resident gay men that are inhabitants of Mexico City, through interviews and some visual documents collected in their social networking sites. Care and time spent with children are approached; then, the link between authority, transmitted values and gender socialization of children is exposed. In general, it is revealed that parental arrangements are in tune with the transformations of contemporary fatherhood; however, they should strengthen some components due to their sexual orientation.